A Conflict Context Reasoning Method Based on Dempster-Shafer Theory in Ubiquitous Computing - Xinkai Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, one conflict context reasoning method based on Dempster-Shafer theory is proposed. Firstly the context conflict problems are illustrated and partitioned based on theory of evidence. Then the context model combined with Dempster-Shafer theory is presented and applied to the reasoning method based on Dempster rule of combination. The effectiveness of this method is verified with a RFID application example. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3136